Incidence and predictors of postoperative ischemic stroke after coronary artery bypass grafting. Issue 5 (6th February 2021) - Mohamed, Mohamed O.; Hirji, Sameer; Mohamed, Walid; Percy, Edward; Braidley, Peter; Chung, Joshua; Aranki, Sary; Mamas, Mamas A.
Abstract: Background: Data on the incidence and outcomes of ischemic stroke in patients undergoing coronary artery bypass grafting (CABG) in the current era are limited. The goal of this study was to examine contemporary trends, predictors, and outcomes of ischemic stroke following CABG in a large nationally representative database over a 12‐year‐period. Methods: The National Inpatient Sample was used to identify all adult (≥18 years) patients who underwent CABG between 2004 and 2015. The incidence and predictors of post‐CABG ischemic stroke were assessed and in‐hospital outcomes of patients with and without post‐CABG stroke were compared. Results: Out of 2 569 597 CABG operations, ischemic stroke occurred in 47 279 (1.8%) patients, with a rising incidence from 2004 (1.2%) to 2015 (2.3%) ( P  < .001). Patient risk profiles increased over time in both cohorts, with higher Charlson comorbidity scores observed amongst stroke patients. Stroke was independently associated with higher rates of in‐hospital mortality (3‐fold), longer lengths of hospital stay (~6 more days), and higher total hospitalisation cost (~$80 000 more). Age ≥60 years and female sex (OR 1.33, 95% CI 1.31‐1.36) were the strongest predictors of stroke (both P  < .001). Further, on‐pump CABG was not an independent predictor of stroke ( P  = .784). Conclusion: In this nationally representative study we have shown that the rates of postoperative stroke complications following CABG have increased over time to commensurate with a parallel increase in overall baseline patient risks. Given the adverse impact of stroke on in‐hospital morbidity and mortality after CABG, further studies are warranted to systematically delineate factors contributing to this striking trend. Abstract :